From The Enlightenment Scientists Mahmudhoja Behbudii - Axmadjonova Gulnoza Rustamjon qizi (Peerian Journals Publishing, 2024)
This article analyzes Mahmudhoja Behbudi, Jadidism, the emergence of the first Jadid schools, and the activities of enlightened scientists.
Keywords: Turkestan; jadidism; school